Travels of Ali Bey, in Morocco, Tripoli, Cyprus, Egypt, Arabia, Syria, and Turkey between the years 1803 and 1807, written by himself and illustrated by maps and numerous plates. - Badia y Leblich, Domingo, 1767-1818. (London)
1. c. (xlii, 339 s., xliv y. resim, plan (kimi katlı), [2] katlı sayfa harita)